PSIKOLOGI KESADARAN GURU DALAM MENERAPKAN PENDIDIKAN INKLUSIF DI KELAS MULTIKULTURAL - Budi Mulya (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study explores the psychological dynamics of teacher mindfulness in implementing inclusive education within multicultural classrooms. In Indonesia’s highly pluralistic society, teacher awareness plays a pivotal role in bridging student diversity and addressing structural barriers to full inclusion. Employing a qualitative phenomenological approach within an interpretive paradigm, the study involved 15 purposively selected teachers from five inclusive schools, representing diverse cultural backgrounds, educational levels, and teaching experiences. Data were collected through in-depth semi-structured interviews, participant observations, and reflective teaching journals, and analyzed using Braun and Clarke’s interpretative thematic analysis. The findings identify three levels of critical teacher consciousness intrapersonal awareness, involving the recognition of unconscious cultural biases and exclusive values; interpersonal awareness, reflected in pedagogical sensitivity and empathy toward diverse student needs; and systemic awareness, marked by an understanding of institutional challenges such as rigid curricula and limited resources. Teachers demonstrating high levels of mindfulness developed creative adaptive strategies, including the redesign of the hidden curriculum, the use of culturally responsive approaches, and building alliances with parents and local communities. These findings underscore the importance of psychological dimensions in the training and professional development of inclusive educators. Accordingly, the study recommends the integration of critical consciousness training based on self-reflection and intercultural dialogue into teacher education curricula and ongoing professional development programs in multicultural school settings.